The Association of Altered Gut Microbiota and Intestinal Mucosal Barrier Integrity in Mice With Heroin Dependence - Yang, Jiqing; Xiong, Pu; Bai, Ling; Zhang, Zunyue; Zhou, Yong; Chen, Cheng; Xie, Zhenrong; Xu, Yu; Chen, Minghui; Wang, Huawei; Zhu, Mei; Yu, Juehua; et al. (Frontiers in Nutrition, 2021)
The gut microbiota is believed to play a significant role in psychological and gastrointestinal symptoms in heroin addicts. However, the underlying mechanism remains largely unknown. We show here that heroin addicts had a decrease in body mass index (BMI) and abnormal serum D-lactic acid (DLA), endotoxin (ET) and diamine oxidase (DAO) levels during their withdrawal stage, suggesting a potential intestinal injury. The gut microbial proﬁles in the mouse model with heroin dependence showed slightly decreased alpha diversity, as well as higher levels of Bifidobacterium and Sutterella and a decrease in Akkermansia at genus level compared to the control group. Fecal microbiota transplantation (FMT) further confirmed that the microbiota altered by heroin dependence was sufficient to impair body weight and intestinal mucosal barrier integrity in recipient mice. Moreover, short-chain fatty acids (SCFAs) profiling revealed that microbiota-derived propionic acid significantly decreased in heroin dependent mice compared to controls. Overall, our study shows that heroin dependence significantly altered gut microbiota and impaired intestinal mucosal barrier integrity in mice, highlighting the role of the gut microbiota in substance use disorders and the pathophysiology of withdrawal symptoms.